Fetal surgery of amniotic bands - Diaz Primera, Ramiro Jesús (2018)
The amniotic band syndrome (ABS) is characterized by accumulation of fibrous tissue bands or strings that adhere to the fetus and may produce compression in different sites. Most cases present multiple congenital anomalies incompatible with life. A small group of fetuses have isolated constrictions of the limb that may cause severe limb dysfunction or limb amputation if not treated during pregnancy. This rare condition occurs in approximately 1:1 200 to 1:15 000 live births. The exact cause of ABS remains uncertain; however, theories of intrinsic, extrinsic and iatrogenic reasons have been proposed. The evolution of the limb affected by ABS is characterized by progression of distal edema due to venous obstruction, and intrauterine amputation of the limb from vascular insufficiency. Fetoscopic release of the amniotic bands through minimally invasive surgery techniques may allow life preservation as well as limb function. Literature review suggests that fetoscopic release of amniotic bands allows preservation of limb function in 50% of cases.